Choice of scale by banks in financial centers - Gulamhussen, M. A. (International Business Review, 2007)
The paper develops a theoretical link between foreign investment, scale and reversibility in the banking industry. This link is used to formulate hypotheses that are empirically examined with a unique data set collected through interviews with senior managers of multinational banks in London. Findings reveal that banks do not set up large operations to service domestic customers or get a foothold, but do so to create hubs. Banks with confident beliefs set up large operations, and use large offices to lock themselves into the market. These results explain the cross-sectional variation in the size of foreign investments in the industry. Robustness checks do not reveal presence of influential data points; regressions are stable over time and consistent with what we know from secondary samples.